2020
DOI: 10.1111/os.12786
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Management of Glenoid and Greater Tuberosity Bipolar Fractures

Abstract: Objective: To report the clinical and radiological outcomes of arthroscopically assisted surgery for combination of glenoid and greater tuberosity fractures after traumatic shoulder dislocation. Methods: From December 2013 to December 2018, patients with concomitant fracture of the greater tuberosity and glenoid who underwent arthroscopically assisted surgery were retrospectively reviewed. Fifteen patients were included. Preoperative computed tomography (CT) scans with 3D reconstruction were performed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In recent years, arthroscopic surgery has been more widely applicable to Ideberg Type IA or IB fractures (IA, IB comminuted fractures, VI fractures), acute anterior and inferior glenoid fractures involving articular surface fractures <30% or multiple bone fragments 7,11,12 . Bauer 13 , 2006, reported the arthroscopic treatment of 5 cases of Ideberg Type IA glenoid fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, arthroscopic surgery has been more widely applicable to Ideberg Type IA or IB fractures (IA, IB comminuted fractures, VI fractures), acute anterior and inferior glenoid fractures involving articular surface fractures <30% or multiple bone fragments 7,11,12 . Bauer 13 , 2006, reported the arthroscopic treatment of 5 cases of Ideberg Type IA glenoid fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The arthroscopic-assisted fixation of the other types of intra-articular scapula fractures has not been extensively studied compared to the Ideberg type III fractures. Zhang et al [106] reported four patients with concomitant Ideberg II glenoid and greater tuberosity fractures who were treated surgically with an arthroscopically assisted fixation procedure. In their surgical technique, the fragment of the inferior glenoid was fixed using two, three, or four suture anchors and a cannulated screw.…”
Section: Other Types Of Glenoid Fossa Fracturesmentioning
confidence: 99%
“…Traumatology is well‐represented and specific specialized solutions are described by highly qualified colleagues from different centers in Quingdao, Shanghai, Tianjin, and Chengdu 8–11 . Technical improvements and solutions in humeral nailing are described by Xiao‐ming Wu from Shanghai 12 .…”
mentioning
confidence: 99%